Elements of Child Welfare Protection in Islamic Family Law in Southeast Asian Countries - Nasohah, Zaini; Zainal Abidin, Raihana; Balqish Saharudin, Nur Izzatun; Megat Khairulazwan, Puteri Noraqilah; Fikri, Fikri (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
The welfare of children is one of the key concerns in matters of marriage and divorce. Issues related to child welfare typically arise in custody disputes following divorce. Almost all Islamic family laws in Muslim countries have legal provisions to ensure child welfare. However, these welfare provisions are often considered unclear due to their general nature. This article aims to highlight the elements of child welfare care that are sought to be manifested through Islamic family law provisions in Southeast Asian Muslim countries. A document analysis method, including case judgments, was used to identify the aspects of welfare that are of concern. The analysis found that some Islamic family law provisions in Southeast Asian countries regarding child welfare remain general in nature. Legal practitioners have attempted to outline the elements of child care through interpretations of existing provisions or through the rationale provided in court judgments. Among the identified welfare elements are priority for the mother, the status quo of the current custodian, the child's age, the child's right to choose, the custodian’s religion, the custodian's lifestyle, economic status of the custodian, health status of the custodian, the custodian’s age, the custodian’s behavior, the custodian's place of residence, and access to the child's education. These elements are typically emphasized by disputing parties when presenting evidence to the court.